O Estado de Minas Gerais e a Pobreza (1898–1920) - Fernandes Braga, Virna Ligia (Review of International American Studies, 2014)
[For English, scroll to the bottom of the page] Virna Ligia Fernandes Braga Universidade Federal de Juiz de Fora Brasil "O Estado de Minas Gerais e a Pobreza (1898–1920)" O artigo analisa as propostas de assistência à pobreza, de âmbito público e privado em Minas Gerais, entre os anos de 1898 e 1920. O recorte temporal abarca uma série documental produzida pela Secretaria do Interior do estado de Minas Gerais – Brasil, e que apresenta valiosas informações sobre a assistência publica desde o pós-abolição até os anos iniciais do século XX. De forma mais específica, trata das alternativas encontradas pelo Estado e sociedade para enfrentar os problemas advindos da chamada ‘questão social’ em Minas Gerais, com ênfase nas políticas sociais do governo. As fontes utilizadas são os Relatórios dos Presidentes da Província de Minas Gerais e, principalmente, o fundo documental da Secretaria do Interior, que se encontra no Arquivo Público Mineiro - APM em Belo Horizonte, MG. Neste fundo documental, série 10 ‘Saúde e Assistência Pública’, foram selecionadas requisições referentes às subvenções concedidas a hospitais, hospícios, casa de caridade, bem como seus relatórios de manutenção. Na maioria das santas casas funcionavam asilos, orfanatos, hospitais, que pediam o auxílio, mediante apresentação do numero de enfermos, asilados, órfãos, o que permite traçar o perfil da assistência pública e privada em Minas Gerais. Palavras-chave: Pobreza; Minas Gerais; documentação "The State of Minas Gerais and Poverty (1898-1920)" This article raises the question of the assistance to the poor delivered both in public and in private contexts in Minas Gerais, during the years 1898–1920. The phenomena of this period have been addressed by the authors of a documentary series produced by the Secretary of the Interior of the State of Minas Gerais, who present valuable information about the public assistance from the proclamation of abolition until the first decades of the 20th century. More specifically, the series deals with the alternatives the state and society sought and found to tackle the problems arising from the so-called ‘social question’ in Minas Gerais, and it places an emphasis on social policies implemented by the government. The sources upon which the documentary is based are the official Reports of the Presidents of the Province of Minas Gerais, and especially the repository of the Secretary of the Interior, held in the Minas Public Archives—APM in Belo Horizonte, MG. In series 10 of the documentary, titled ‘Health and Public Assistance’, one finds information related to subventions granted to hospitals, asylums and charity shelters, as well as data concering their maintenance reports. Most church-based organizations running nursing homes, orphanages and hospitals, would be granted assistance upon presentation of the number of the sick, asylees, or orphans in their care. Such data allows one to trace and reconstruct the profile of public and private assistance in Minas Gerais. Keywords: Poverty; Minas Gerais; documentary series